A study of compliant-based actuators for passive-active vibration control in vehicle suspension system - Mareta, Sannia (2017)
This work proposes a method for controlling vibration transmissibility using compliant-based actuators. The compliant actuator combines a conventional actuator with elastic elements in a series configuration, such as passive springs, with the aim of controlling the vibration at important low frequencies. In contrast to the rigid actuator, a compliant actuator provides better accuracy and robustness for force control. At high frequencies, the actuator behaves like a passive spring with low impedance, providing lower output impedance and better shock resistance to the actuator than the stiff actuator. The benefits of compliant actuators for vibration control applications, demonstrated in this work, are twofold: (i) vibration reduction over a wide frequency bandwidth by passive control means; (ii) improvement of vibration control performance when active control is applied using the compliant actuator. The vibration control performance is compared with the control performance achieved using the well-known vibration absorber and conventional rigid actuator systems. The performance comparison showed that the compliant actuator provided a better flexibility in achieving vibration control over a certain frequency bandwidth. The investigation on passive and active control characteristics of the compliant actuator are conducted in relation to the compliant stiffness and damping parameters, which reveal a strong influence of the parameters to the overall passive-active vibration suppression performance.